Use of the LCM Model in the prospective simulation of land use in the Nafoun watershed (Northern Ivory Coast) - Kamagate Anzoumanan; Koffi Ehouman Serge; Koffi Yao Blaise (E3S Web of Conferences)
Land use change is known worldwide as a driver of environmental change. Environmental change assessment is the most accurate method for understanding land use, the types of change to be estimated, and the forces and evolutions driving these changes. The aim of the study is to assess the temporal and spatial dynamics of land use change and to predict the future using Landsat images. The Land Change Modeler (LCM) was therefore used. LCM is a module integrated into a Geographic Information System (GIS) and TerrSet geospatial modeling system, assimilated to the Multi- Layer Perceptron (MLP) and the CA_Markov chain for analysis and prediction of land use change and assessment of environmental implications. LCM forward modeling relies on two types of input maps: (1) land cover maps at previous times and (2) explanatory variable maps. Our study area is the Nafoun watershed in the Poro region of northern Côte d'Ivoire. Landsat images from 1986, 2000 and 2023 were used to assess and predict the spatio- temporal distributions of land use change. The historical results show that from 1986 to 2023, two trends were observed in the evolution of the different land cover classes in the Nafoun watershed. The first trend is regressive and concerns forests, savannahs, water and habitats/bare ground. The second trend is progressive and concerns crops, whose surface area has practically increased tenfold, from 8.31 to 78.15 km2. The land-use map of the Nafoun watershed to 2070 in the deforestation scenario shows a trend towards an increase in agricultural areas and bare habitats/soils, and a decrease in savannah, forest and water areas. However, in the reforestation scenario, the forest and savannah class have increased significantly, while the area of habitats/bare ground has decreased. In this scenario, a sound environmental protection policy would play a positive role in the conservation of natural plant resources.